Food tourism and events as tools for social sustainability?. Issue 3 (30th May 2018) - de Jong, Anna; Varley, Peter
Abstract : Purpose: Food tourism and events are often prefaced as tools for sustainability within national and intra-national food and agricultural policy contexts. Yet, the realities of enhancing sustainability through food tourism and events are problematic. Sustainability itself is often conceived broadly within policy proclaiming the benefits of food tourism and events, with a need for further deconstruction of the ways each dimension of sustainability – economic, environmental, social and cultural – independently enhances sustainability. The lack of clarity concerning the conceptual utilisation of sustainability works to compromise its value and utilisation for the development of food tourism and events in peripheral areas. In recognition, this paper aims to turn attention to social sustainability within the context of a local food festival, to ask the following: in what ways is social sustainability enhanced through a local food festival, who benefits from this sustainability, and how? Design/methodology/approach: The paper examines the development of a local food festival in a rural coastal community on Scotland's west coast. The concept of social capital is used to examine the unfolding power relations between committee members, as well as the committee and other social groups. Observant participation undertaken over a 10-month period, between December 2015 and September 2016, renders insights into the ways event planning processes were dependent on the pre-existing accruement of social capital by certain individuals and groups. Findings: Local food festivals have the potential to enhance social sustainability, in offering opportunity to bridge relations across certain diverse groups and foster an environment conducive to cohabitation. Bridging, however, is dependent on preconceived social capital and power relations, which somewhat inhibits social integration for all members of a community. The temporally confined characteristics of events generates difficulties in overcoming the uneven enhancement of social sustainability. Care, thus, needs to be upheld in resolutely claiming enhancement of social sustainability through local food events. Further, broad conceptualisations of "community" need to be challenged during event planning processes; for it is difficult to develop a socially inclusive approach that ensures integration for diverse segments without recognising what constitutes a specific "community". Originality/value: This paper is situated within the context of a peripheral yet growing body of literature exploring the potential of events to develop social sustainability. In extending work examining events and social sustainaility the paper turns attention to the gastronomic – examining the extent to which social sustainability is enhanced through a local food festival, for a rural coastal community – Mallaig, on Scotland's west coast.